2011
DOI: 10.1525/boom.2011.1.4.54
|View full text |Cite
|
Sign up to set email alerts
|

Amnesty or Abolition?

Abstract: Convicts and undocumented immigrants are similarly excluded from full social and political membership in the United States. Disfranchised, denied core protections of the social welfare state and subject to forced removal from their homes, families, and communities, convicts and undocumented immigrants, together, occupy the caste of outsiders living within the United States. This essay explores the rise of the criminal justice and immigration control systems that frame the caste of outsiders. Reaching back to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Most scholarship was on post-1848 history that centered the Chicanx experience on the US—Mexico borderlands. The focus was on White and Chicanx relations, it evacuated other groups even as scholars have shown that this mapping was more complicated (Gomez, 2008; Guidotti-Hernández, 2011). Of course, a broader reading of history in Las Americas—one that acknowledges the African diaspora that enabled US and European capitalism to flourish as a world system—necessitates placing Blackness as central to Latin American history.…”
Section: Locating Black and Brown Solidarity In The Early 21st Centurymentioning
confidence: 99%
See 1 more Smart Citation
“…Most scholarship was on post-1848 history that centered the Chicanx experience on the US—Mexico borderlands. The focus was on White and Chicanx relations, it evacuated other groups even as scholars have shown that this mapping was more complicated (Gomez, 2008; Guidotti-Hernández, 2011). Of course, a broader reading of history in Las Americas—one that acknowledges the African diaspora that enabled US and European capitalism to flourish as a world system—necessitates placing Blackness as central to Latin American history.…”
Section: Locating Black and Brown Solidarity In The Early 21st Centurymentioning
confidence: 99%
“…Formed in 1987, CR’s mission is to abolish prisons. While deeply rooted in the BRT, CR reaches out to all persons and groups interested in fighting the prison-industrial complex, including Latinxs, as they are now the largest racial/ethnic group in Federal prisons (Hernández, 2011). CR also has chapters in Los Angeles and New Orleans.…”
Section: Mapping the Geographical Dimensions Of Solidaritymentioning
confidence: 99%
“…Although people of every racialized category are imprisoned, the majority of state and federal prisoners in the US are Black and brown; just 35% of sentenced prisoners in the US were white in 2019 (Carson, 2020). The “alienated citizens and criminalized immigrants” targeted with these forms of control together constituted what Kelly Lytle Hernández (2011: 55) calls a “racialized caste of outsiders,” disproportionately subject to state-sanctioned force in the criminal punishment and immigration enforcement systems.…”
Section: Background and Frameworkmentioning
confidence: 99%
“…Resistance to imigration enforcement has a long history in the US (cf. Hernández, 2010; Loyd & Mountz, 2018; Ordaz, 2021). In the twenty-first century, these consolidated into a movement that gained mainstream and national attention.…”
Section: Background and Frameworkmentioning
confidence: 99%